Indonesian Pre-Service English Teachers’ Perceived Challenges in Improving English Oral Communication Skills - Abid (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2018)
The study investigates perceived challenges that pre-service teachers (henceforth refers to PSTs) majoring in an English Education Program of a state university in the Province of Gorontalo, Indonesia, experience in improving their English oral proficiency level. Data from the PSTs were collected mainly using individual semistructured interviews, and then corroborated with the interview results collected from several lecturers who participated voluntarily. Informed by a thematic analysis approach, the study shows that the PSTs reported three main areas of challenges; linguistic proficiency, socio-culture, and English language engagement opportunity. Recommendations seeking to assist PSTs as well as the English Education Program in anticipating such challenges are also addressed.